2013
DOI: 10.3168/jds.2012-6487
|View full text |Cite
|
Sign up to set email alerts
|

Elimination kinetics of cephapirin sodium in milk after an 8-day extended therapy program of daily intramammary infusion in healthy lactating Holstein-Friesian cows

Abstract: The objective of this study was to determine the elimination kinetics of extended therapy with intramammary (IMM) cephapirin in lactating dairy cattle. Eight healthy Holstein-Friesian cows were administered cephapirin (200mg) into all 4 mammary glands every 24 h after milking. Cows were milked 3 times per day and concentrations of cephapirin and desacetyl cephapirin were determined in bucket milk using liquid chromatography-mass spectrometry. Milk concentration-time data after the last of the 8 IMM infusions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Also, with time, conversion of cephapirin to its major metabolite desacetyl cephapirin is likely. Within 24 h of intramammary infusion of cephapirin in lactating cows >50% of infused cephapirin was converted to desacetyl cephapirin [3], [48].…”
Section: Resultsmentioning
confidence: 99%
“…Also, with time, conversion of cephapirin to its major metabolite desacetyl cephapirin is likely. Within 24 h of intramammary infusion of cephapirin in lactating cows >50% of infused cephapirin was converted to desacetyl cephapirin [3], [48].…”
Section: Resultsmentioning
confidence: 99%
“…According to data from the 2007 NAHMS survey, more than 92.5% of dairy operations milk cows twice a day (USDA-APHIS, 2008). However, a growing number of dairy producers are increasing their milking frequency from twice to 3 times per day (3×) to improve milk production (Pearson et al, 1979;Smith et al, 2002;Hale et al, 2003). When producers treat mastitis in cows milked 3×, it is difficult to know what the proper dosing interval for intramammary antibiotics should be to maintain adequate therapeutic drug concentrations in the mammary gland.…”
Section: Short Communicationmentioning
confidence: 99%
“…Therefore, from a clinical view, it is critical to generate pharmacokinetic data on intramammary antibiotics in cattle milked 3× to help determine appropriate dosing intervals for producers. Past studies demonstrated that milking frequency did not affect the length of time that milk drug concentrations exceeded the MIC values when intramammary cephapirin was administered to dairy cows (Stockler et al, 2009a;Gorden et al, 2013). However, no data exist on the pharmacokinetics of intramammary hetacillin in dairy cattle.…”
Section: Short Communicationmentioning
confidence: 99%
“…For bovine mastitis episodes caused by highly contagious staphylococci or streptococci, an intramammary infusion (IMM) of antimicrobial agents is usually used to treat clinical mastitis[ 4 , 5 ]. This treatment has been confirmed as having a good therapeutic effect as an antimicrobial agent, and it can attain and maintain an adequate and effective drug concentration at the site of infection in mammary tissue [ 6 , 7 ]. Ceftiofur is a broad-spectrum, third-generation cephalosporin antibiotic for veterinary use.…”
Section: Introductionmentioning
confidence: 99%